Artificial ponds do not support the natural functional and taxonomic composition of alpine dragon- and damselfly communities - Felix Puff; Christian H. Schulze; Roberto Novella-Fernandez; Andreas Hilpold; Stefan Pinkert; Elia Guariento (Global Ecology and Conservation, 2025)
Alpine regions host diverse habitats and rich biodiversity. Yet, aquatic environments, crucial for many threatened alpine species, are underrepresented in conservation throughout the Alps. Among many factors, anthropogenization impacts alpine aquatic ecosystems. While anthropogenic ponds are proposed for biodiversity support, their suitability for the natural alpine freshwater biota remains unclear. Dragonflies and damselflies, with their ectothermic physiology and semi-aquatic life cycle, are greatly constrained by both temperature and habitat features, thus potentially facing additive constraints in alpine artificial waters. This study investigated Odonata communities in artificial and natural water bodies at 41 different elevations, analyzing abundance, diversity and traits associated with thermoregulation (body size and color lightness), life history (voltinism) and habitat preference (thermophily and habitat breadth). Temperature differently affected traits related to thermoregulation in dragonfly and damselfly communities, with an increase in body size and decrease in color lightness along decreasing temperature (i.e. increasing elevation) in dragonflies and an increase in color lightness in damselflies. Concurringly, damselfly abundances strongly decreased towards cold temperatures. In both suborders thermophily and habitat breadth decreased with decreasing temperature, but these trends were less pronounced in anthropogenic sites. Trait variation of dragonflies follows trends predicted by thermal melanism and Bergmann’s rule, while the absence of such trends in damselflies suggest limited thermoregulatory potential. The additive constraints of temperature and anthropogenic disturbance in alpine anthropogenic sites prevent alpine species to utilize such water bodies and challenges their potential for nature conservation in the face of global warming and biodiversity decline.